(untitled) (Revista Estudios Psicológicos, 2022)
This article clarifies the psychosocial causes that affect the permanence of women in sentimental relationships with domestic violence through a descriptive-qualitative study. The results show that the factors underlying this phenomenon are psychological (cognitive distortions, irrational beliefs, emotional dependence, insecure attachment and paradoxical adaptation to violence) and sociodemographic (economic dependence, educational level, number of children and years of abuse). In conclusion, this theoretical review suggests multidisciplinary studies that provide effective tools for prevention and intervention in clinical practice.